1998
DOI: 10.1164/ajrccm.158.3.9711076
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Indicators for Blood and Marrow Transplant Patients Admitted to an Intensive Care Unit

Abstract: Although hematopoietic stem cell transplantation (HSCT) can be curative in patients with certain malignancies, survival is poor if the recipient becomes critically ill. This prospective study examined the outcomes of 115 consecutive HSCT patients admitted to the medical intensive care unit (MICU) of a tertiary cancer center and identified variables associated with survival. The need for endotracheal intubation and mechanical ventilation ("intubation") had a profound adverse effect on survival. Overall, 9 of 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
113
3
7

Year Published

2003
2003
2011
2011

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(134 citation statements)
references
References 28 publications
11
113
3
7
Order By: Relevance
“…For instance, of the 112 patients with hematological malignancies ventilated in our centre > 7 days between 1997 and 2007, 26% survived to hospital discharge and 20% were still alive at 6 months (unpublished data). However, the survival of ventilated allogeneic bone marrow or peripheral stem cell transplantation recipients remains particularly poor [19][20][21] although some improvement has been achieved [36][37][38] . Encouraging results have also been obtained in cancer patients requiring renal replacement therapy for acute renal failure, even in case of multiple organ failure or in combination with ventilatory support [33][34][35][36] .…”
Section: Outcome In Critically Ill Cancer Patients: Evolution Over Thmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, of the 112 patients with hematological malignancies ventilated in our centre > 7 days between 1997 and 2007, 26% survived to hospital discharge and 20% were still alive at 6 months (unpublished data). However, the survival of ventilated allogeneic bone marrow or peripheral stem cell transplantation recipients remains particularly poor [19][20][21] although some improvement has been achieved [36][37][38] . Encouraging results have also been obtained in cancer patients requiring renal replacement therapy for acute renal failure, even in case of multiple organ failure or in combination with ventilatory support [33][34][35][36] .…”
Section: Outcome In Critically Ill Cancer Patients: Evolution Over Thmentioning
confidence: 99%
“…However, the survival of ventilated allogeneic bone marrow or peripheral stem cell transplantation recipients remains particularly poor [19][20][21] although some improvement has been achieved [36][37][38] . Encouraging results have also been obtained in cancer patients requiring renal replacement therapy for acute renal failure, even in case of multiple organ failure or in combination with ventilatory support [33][34][35][36] . While renal replacement therapy was unequivocally associated with a 90-95% ICU mortality in case of multiple organ failure two decades ago 12,18 , Soares et al 31 recently reported 65% six month mortality in patients with one or two associated organ failures and a 93% six month mortality in case of 3 associated organ failures, again similar to general ICU patients 32 .…”
Section: Outcome In Critically Ill Cancer Patients: Evolution Over Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal (venoocclusive hepatic insufficiency, gastric bleeding), neurological (metabolic encephalopathy, hemorrhages), and cardiac disorders (drug toxicity, pericardial effusion), in addition to coagulopathies and renal insufficiency are the most common complications in transplant recipients that might need intensive care. 50 …”
Section: Bone Marrow Transplantmentioning
confidence: 99%
“…Nas UTI em que o uso do SAPSII é frequente, estima-se que 20 a 40% dos pacientes submetidos a TCTH autólogo e alogênico necessitem de cuidados intensivos (63) e cuja taxa de mortalidade hospitalar varia de 54-96% (55,64) .…”
Section: Mortalidade No Tcth: Taxa E Preditoresunclassified